2010
DOI: 10.1002/cjce.20253
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of polycyclic aromatic hydrocarbons: Model simulation for bioavailability and biodegradation

Abstract: A mathematical model for a one-dimensional convective-dispersive solute transport in a soil matrix is presented. The interplay of linear equilibrium sorption and first order degradation were incorporated into the formulation of the model. The model took into consideration the overall effects of the solid and liquid phase mass transfer resistances. Data from experiments were analysed using the temporal moments method (MOM) and CXTFIT curve-fitting technique. The functional parameters; dispersion coefficient, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This could be traced to the phenomenon of surface adsorption/desorption effects of naphthalene on soil organic carbon and interstitial voids within the micro and sub-micro pores of the soil particle. Reports have also shown that less than the total amount of some aromatics such as naphthalene adsorbed onto soil particles are actually desorbed and released (Nkedi-Kizza et al, 2006;Owabor and Agarry, 2009;Owabor et al, 2010;Owabor et al, 2011). This may therefore, limits their bioavailability for microbial degradation.…”
Section: Discussionmentioning
confidence: 99%
“…This could be traced to the phenomenon of surface adsorption/desorption effects of naphthalene on soil organic carbon and interstitial voids within the micro and sub-micro pores of the soil particle. Reports have also shown that less than the total amount of some aromatics such as naphthalene adsorbed onto soil particles are actually desorbed and released (Nkedi-Kizza et al, 2006;Owabor and Agarry, 2009;Owabor et al, 2010;Owabor et al, 2011). This may therefore, limits their bioavailability for microbial degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this premise is that the small pore spaces internal to aggregates of soil and sediment particles exclude microbes, such that compounds that are dissolved or sorbed within these immobile-water domains must first be transported to the external aqueous phase (i.e., bulk aqueous phase) before they can be metabolized [5]. This premise is supported by several laboratory studies that have found biodegradation to occur only, or predominantly, in the bulk aqueous phase [6], [7]. A variety of factors, including physical characteristics of the sorbent (e.g., particle shapes, sizes, and internal porosities), chemical properties of the sorbates and sorbents, and biological factors (e.g., microbial abundance and affinity for the contaminant) influence availability.…”
Section: Applications In Soil Remediationmentioning
confidence: 98%
“…Studies on mass transfer effects for the evaluation of bioavailability and biodegradation parameters of contaminant solutes in aqueous solid/sediment matrix applicable for biodegradation of the environmentally persistent and recalcitrant chemicals have been extensively investigated using models [7], [9] which incorporates a two-site sorption/desorption kinetics.…”
Section: Applications In Soil Remediationmentioning
confidence: 99%
“…Naphthalene and anthracene transport through a saturated and homogeneous porous media in onedimensional uniform flow considering convection, dispersion, linear equilibrium sorption, and firstorder degradation has been described in our earlier paper (Owabor et al 2003). The unsteadystate models characterizing the reactions in both macroporous and microporous systems are intended to predict the concentration in the axial (z) and radial (r) directions using the experimental data from a soil microcosm reactor.…”
Section: Unsteady-state Modelmentioning
confidence: 99%